2010
DOI: 10.1128/jcm.02167-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Mycobacterium tuberculosis Isolates from a Tertiary Care Tuberculosis Hospital in South Korea

Abstract: 960, 1955, 2163b, 2165, 2996, 3192, 4052, and 4348) (h ‫؍‬ 0.98) that was able to differentiate most of the closely related strains was identified. These findings suggest that 24-locus-based MIRU-VNTR typing is a likely suitable alternative to RFLP to differentiate clinical isolates in this setting, which is dominated by M. tuberculosis Beijing strains. Within the study limits, our results also suggest that the problem of drug-resistant TB in the Republic of Korea may be largely due to acquired resistance as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 41 publications
4
48
0
3
Order By: Relevance
“…In fact, MIRU-VNTRs also differentiated two isolates present in a single 12-banded IS6110-RFLP cluster into unique types. Though unusual for high-banded strains, similar findings have been reported by other investigators who reported isolates within IS6110-RFLP clusters that differed by two-seven loci in a 24 loci MIRU-VNTR assay (Shamputa et al 2010). We used primers for 11 loci from the original set of 12 loci used in earlier studies (Supply et al 2000).…”
Section: Discussionmentioning
confidence: 62%
“…In fact, MIRU-VNTRs also differentiated two isolates present in a single 12-banded IS6110-RFLP cluster into unique types. Though unusual for high-banded strains, similar findings have been reported by other investigators who reported isolates within IS6110-RFLP clusters that differed by two-seven loci in a 24 loci MIRU-VNTR assay (Shamputa et al 2010). We used primers for 11 loci from the original set of 12 loci used in earlier studies (Supply et al 2000).…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Hanekom and colleagues reported that even 15-and 24-loci MIRU-VNTR typing has a reduced discriminatory power compared to IS6110 typing for strains of the Beijing lineage in Cape Town, South Africa, and that the inclusion of more variable loci might be necessary to reach the same level as that with IS6110 RFLP typing (7). As an exception, Shamputa et al found a similar discriminatory power of 24-loci MIRU-VNTR and IS6110 RFLP typing on Korean Beijing strains and suggested that 24-loci-based MIRU-VNTR typing is a likely suitable alternative to RFLP to differentiate clinical isolates in their setting dominated by Beijing strains (15).…”
Section: Discussionmentioning
confidence: 95%
“…In comparative populationbased evaluations, we and others found a similar if not slightly better performance of 15-or 24-loci MIRU-VNTR typing compared to IS6110 RFLP typing for discrimination of clinical isolates and detection of transmission chains in TB patient populations (13). Few subsequent studies compared MIRU-VNTR typing with the "gold standard" IS6110 RFLP typing, because the latter is rather laborious and more difficult to perform (6,7,15). The majority of the studies confirmed the initial finding that 24-loci MIRU typing can be used for MTBC genotyping with a similar performance as IS6110 typing, but some studies suggested a lower discriminatory power of 24-loci MIRU-VNTR typing in settings where Beijing strains are dominant (7,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, such stochastic evolution can explain some degree of discordance between results of different genotyping methods among very closely related strains over short evolutionary distances (8). Over longer genetic distances, in populations of more distantly related strains, a higher correlation is apparent as a reflection of the clonal evolution of M. tuberculosis (15,22).…”
Section: Figurementioning
confidence: 99%